The Relationship Between Wudhu With Language - yusni sinaga (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Taking wudhu’ means draines water to certain body organs as commanded by Allah Swt and His Prophet Rosulullah Saw whereas language means using one of the organs of the body as the vocal cards as explained in the previous language discussion before, they are ear in listening, mouth in speaking or head and face organs hands and will be given a reaction that will involved movement of the whole body including the two feets. All organs of the body that will be used in language specifically are also organs that must be cleaned in implementation of the taking wudhu’. That’s way, people who actually take wudhu’, people who often keeps wudhu’ and people who stay in wudhu’ will bring peace and luck to themselves and other people in their environment while they are taking communication and interactions.